Secondary Glaucomas - Loayza-Gamboa, Waldo (2023)
Secondary glaucomas (GS) are a group of glaucomas caused by systemic factors or ocular disorders that produce ocular hypertension and subsequent optic nerve damage. The etiologies are very varied and range from ocular trauma, uveitic, pseudoexfoliative, induced by ocular surgeries, diabetic retinopathy, induced by the lens, related to medications (mainly corticosteroids), tumors, among others. It is estimated that there are about 6 million people who have GS compared to the 67 million people with primary glaucoma around the world. From the epidemiological and medical intervention point of view, those secondary to pseudoexfoliation, neovascular and uveitic will stand out. We carry out an updated review, with the latest epidemiological reports and advances in genetics of these 3 presentations, in addition to the latest pharmacological and surgical treatment modalities.